Enhanced environmental sustainability of 3D-printed concrete mixtures based on calcium sulfoaluminate (CSA) and blast furnace cement (CEM III/B) - Senf Ferdinand; Javed Rezan; Funke Henrik; Gelbrich Sandra (MATEC Web of Conferences, 2025)
In response to the environmental challenges associated with ordinary Portland cement production, this research focuses on the development of concrete mixtures based on calcium sulfoaluminate (CSA) cement in combination with blast furnace cement (CEM III/B) for use in the extrusion process (3D printing process). For a targeted 3D printing processing window of 90 minutes, the setting time can be precisely controlled and actively adjusted through the use of retarders such as citric acid, tartaric acid, and phosphate. Among all tested retarders, the combination of tartaric acid and phosphate, each at 0.60 wt% of the total cement mass in concrete mixtures containing 30 wt% CSA and 70 wt% CEM III/B, resulted in the highest early compressive strength of approximately 96 % and the highest 28-day compressive strength of approximately 55 % compared to the mixture without any retardation. Isothermal calorimetry, SEM analysis, and thermogravimetric analysis revealed that the decrease in 28-day strength is attributed to the retardation of both CSA and Portland clinker hydration. As a result, the hydration of the blast furnace slag is initially prevented due to the absence of Portlandite. The 3D printing process using 30 wt% CSA in combination with 70 wt% CEM III/B concrete mixtures demonstrated directional compressive strengths that were approximately 8 % higher for loads applied perpendicular to the printed layers compared to parallel loads. The controlled fast setting through retarders, combined with high early strengths and stable long-term strength development, enables the continuous production of multiple precast concrete elements in quick succession using CSA and CEM III/B mixtures.